Kebijakan Pidana Mati Terhadap Pelaku Tindak Pidana Narkotika Di Lingkungan Prajurit TNI - Sutejo; Mohammad Saleh (Dinasti Review Publisher, 2024)
Regulation on the eradication and countermeasures of narcotics and psychotropic substances (drugs) in Indonesia is known for very strict sanctions in the form of death penalty for drug dealers and dealers who meet certain criteria. Globally, death penalty sanctions pose pros and cons. For those who are against the death penalty is considered contrary to human rights values, while for those who are pro, consider that human rights have restrictions, namely respect for other human rights. In law enforcement against TNI soldiers involved in the circulation of narcotics and psychotropic substances, in addition to being guided by the criminal law that applies to everyone, there are also additional criminal sanctions stipulated in the Criminal Code. In addition, the thing that differentiates is the mechanism and procedure. For the general public, it is processed through the general court, while for soldiers it is processed through the military justice mechanism. The development of death penalty sanctions has shifted with the promulgation of Law No. 1 of 2023 concerning the Criminal Code which will take effect from January 2, 2026.